2013
DOI: 10.1371/journal.pone.0073629
|View full text |Cite
|
Sign up to set email alerts
|

Human fMRI Reveals That Delayed Action Re-Recruits Visual Perception

Abstract: Behavioral and neuropsychological research suggests that delayed actions rely on different neural substrates than immediate actions; however, the specific brain areas implicated in the two types of actions remain unknown. We used functional magnetic resonance imaging (fMRI) to measure human brain activation during delayed grasping and reaching. Specifically, we examined activation during visual stimulation and action execution separated by a 18-s delay interval in which subjects had to remember an intended act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 80 publications
10
88
0
1
Order By: Relevance
“…In contrast, head movements for at least some participants are likely to exceed this amount in studies such as the current one that involve naïve older controls, patients, and a task that requires arm movements. Nonetheless, the amount of movement that we have reported is comparable to other studies that involve arm (or leg) movements within the scanner (Gallivan, McLean, Flanagan, et al, 2013;Singhal, Monaco, Kaufman, & Culham, 2013) and is within the limits of what could reasonably be corrected by motion correction algorithms.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, head movements for at least some participants are likely to exceed this amount in studies such as the current one that involve naïve older controls, patients, and a task that requires arm movements. Nonetheless, the amount of movement that we have reported is comparable to other studies that involve arm (or leg) movements within the scanner (Gallivan, McLean, Flanagan, et al, 2013;Singhal, Monaco, Kaufman, & Culham, 2013) and is within the limits of what could reasonably be corrected by motion correction algorithms.…”
Section: Discussionsupporting
confidence: 83%
“…A memory-guided grasping experiment without illusions, performed in an fMRI scanner, showed that LOC was active during the presentation of the stimulus, but also at the time of action. This suggests that the ventral stream is re-activated to provide relevant information about object properties to guide the dorsal stream in performing the action (Singhal et al, 2013). Given these findings, the effects that we see in the IPS may be the result of direct interactions with LOC.…”
Section: Saccade-and Illusion-related Activationmentioning
confidence: 59%
“…Accordingly, (at least some) detection of action possibilities is not only dorsal, but results from an interstream interaction for off-line visual processing. Accordingly, we know that dorsal perception encodes action possibilities (unconsciously), whereas ventral perception does this consciously (Young, 2006), following object semantic categorization (Gallese, 2007: 3) -for an important analysis of how dorsal and ventral vision interact in vision-for-action, especially in the case of delayed grasping with respect to action guided by memory-stored information see (Singhal, Culham, Chinellato, & Goodale, 2007;Singhal, Monaco, Kaufman, & Culham, 2013; concerning interaction in attention see Adamo & Ferber, 2009; cfr. with my Section 5.3).…”
Section: The Dorsal/ventral Interplay In Actionmentioning
confidence: 99%